BABANDINGAN DONGÉNG SANG RAJA PUTRI SARENG SADÉRÉKNA DUAWELAS KARYA LASMININGRAT, "THE TWELVE BROTHERS", JEUNG "DUA BELAS BERSAUDARA" KARYA JACOB GRIMM (Ulikan Struktural jeung Sastra Bandingan) - Santiah, - (2021)
Jacob Grimm's fairy tales are world-famous literary works, therefore many authors have translated it into various languages, such as into Sundanese, English, and Indonesian. The purpose of this study is to compare the structure of the tales titled Sang Raja Putri sareng Sadérékna Duawelas by Lasminingrat, "The Twelve Brothers" by Jack Zipes, and "Dua Belas Bersaudara" by Kuncoro and Audrey. Stanton and Endraswara were theories used to compare the structure of the tales, while Thompson's theory was used to find its index motive. A qualitative descriptive method was used as the approach of the study. In collecting the data, this study used literature study technique, while analysis technique was used in processing the data. The structures compared in the tales were themes, facts, and settings. The results showed that the three tales had the same storyline from the first to the fourth part. The difference was, the storyline of Sang Raja Putri sareng Sadérékna Duawelas was more detailed than others followed by an additional part and ended with a happy ending story. Meanwhile, "The Twelve Brothers" was more sadistic and the story was simpler than others. "The Twelve Brothers" and "Dua Belas Bersaudara" had a lot of similarities such as theme, plot, setting, social setting, the charcters, and title. On the other hand, the time setting in Sang Raja Putri sareng Sadérékna Duawelas and "Dua Belas Bersaudara" were also the same. In conclusion, the story of "The Twelve Brothers" and "Dua Belas Bersaudara" is more similar. Then, the index motive that was found in the tales was the transformation motive.